Edgar Lawrence Doctorow; a Political Novelist? - Marandi, Seyyed Mohammad; Ramin, Zohreh (Richtmann Publishing, 2012)
Edgar Lawrence Doctorow is generally regarded as a postmodern historical novelist who mingles the marvelous withthe real. His novels are mainly set in the American past. The novels are greatly indebted to historical events and personages butengagement with documentary history is not Doctorow's prime obsession. Critics are at odds in deciding upon the paradox inDoctorow's novels; whether he is a politically minded novelist or an aesthetically obsessed one. Acknowledging the strongpolitical tendencies in Doctorow's novels, many critics claim his enthusiasm and passion for the act of writing finally outweighsthe political inclination of the novels. Identifying Historigraphic metafiction as Doctorow's favorite and repeated technique invirtually all his novels, the present reading wishes to observe the novellas from a contrasting perspective.